Analisis Struktur Narasi dan Nilai Religius Pada Novel “Cinta Dalam Diam” Karya Shineeminka - Sarah Isah Sogalrey (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Literary works are created as a result of experiences, thoughts, and cultural recordings of things that happen to the author. While the novel is one of the literary works, which plays an important role in providing possibilities to address the secrets of human life. In general, what attracts readers in reading a novel is the story. This study aims to describe and explain: (1) The structure in the novel Cinta Dalam Diam Karya Shineminka (2) The religious value in the novel Cinta Dalam Diam Karya Shineeminka. This research uses literary psychology. The approach used in this research is descriptive qualitative research. The data in this study are words, sentences in the form of expressions, and dialog between characters that are the focus of research. The data sources in this research are source documents, such as literary theory books, literary psychology, and the novel Cinta Dalam Diam Karya Shineeminka. The technique used in this research uses data collection through literature study and note-taking techniques and uses the theoretical framework of structural and pragmatic approaches.